The Pauline Concept of Original Sin, in Light of Rabbinic Background - Porter, Stanley E. (Tyndale bulletin, 1990)
Paul’s view of the origins of sin is independent of the rabbinic formulation; he puts forward his own view of sin's origin in 1 Corinthians 15:20-22 and especially Romans 5:12-21.